2014
DOI: 10.3892/mmr.2014.2430
|View full text |Cite
|
Sign up to set email alerts
|

Decreased osteoclastogenesis, osteoblastogenesis and low bone mass in a mouse model of type 2 diabetes

Abstract: Abstract. The effect of type 2 diabetes mellitus (T2DM) on bone is controversial. Therefore, the present study investigated whether T2DM causes osteoporosis and explored the underlying mechanisms involved in this process. The effects of T2DM on bone physiology were analyzed in a mouse model of T2DM; KK/Upj-Ay/J (KK-Ay) mice develop diabetes after 8 weeks and exhibit stable diabetes symptoms and signs after 10 weeks when fed a KK-Ay mouse maintenance fodder. Diabetic mice exhibited hyperglycemia, hyperinsulinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…In humans, biochemical markers and bone histomorphometry reveal a low bone turnover in T2DM (9, 10, 11, 12, 13). In animals, however, low bone formation is also a characteristic of T2DM, while bone resorption parameters are usually increased (14, 15, 16, 17, 18). At a structural level, the accumulation of advanced glycation end (AGE) products under diabetic conditions has been proposed to alter collagen structure and contribute to impaired material properties.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, biochemical markers and bone histomorphometry reveal a low bone turnover in T2DM (9, 10, 11, 12, 13). In animals, however, low bone formation is also a characteristic of T2DM, while bone resorption parameters are usually increased (14, 15, 16, 17, 18). At a structural level, the accumulation of advanced glycation end (AGE) products under diabetic conditions has been proposed to alter collagen structure and contribute to impaired material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, how T2DM affects bone is still controversial. Several mechanisms may be involved, such as direct effects of insulin resistance and hyperglycemia on the bone and bone marrow microenvironment, advanced glycation end products of bone matrix proteins, abnormal cytokine production, and impaired neuromuscular/skeletal interactions [ 4 , 5 ]. Obesity associated with T2DM may be a confounder due to its controversial effect on bone per se (see Dolan et al, 2017 for a comprehensive review) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to non-diabetic male ddY mice, male KK-A y mice had lower areal BMD at the proximal femur, not at the mid-shaft, by 18 weeks of age [32]. However, when using non-diabetic C57BL/6 for controls, Xu et al observed lower volumetric BMD and lower structural strength in bending of the tibia mid-shaft for the diabetic KK-A y mice [33]. Yet another study comparing male KK-A y to male C57BL/6 mice observed higher areal BMD of the whole femur, lower volumetric BMD of trabecular bone in the distal femur, and higher volumetric BMD of cortical bone in the distal femur [34].…”
Section: Introductionmentioning
confidence: 99%